Strategic Channel Management of Saint Bernhard Winery: Direct Versus Indirect Sales - Marc Dressler (Wine Business Journal, 2018)
The case explores the marketing strategy of a German winery with a focus on sales and channel management. Mr. Voss, the CEO of a state-owned winery and the central character of the case has realized a turn-around of the winery in the last ten years. He raised the quality of the wines and increased the productivity of the estate. Saint Bernhard thereby grew in size and wine output with strong extension of the sales channels. Volatility in annual yields, lower yields compared to other wine regions, unforeseeable costs, and disadvantageous regional reputation jeopardized the financial benefits of the restructuring. While direct to consumer sales have been the cornerstone of the business model, decreasing customer loyalty and the need for growth made Mr. Voss turn towards indirect sales channels (B2B), selling via retail partners or restaurants. The expansion secured the sales of additional production of Saint Bernhard’s wines. Apparently, the strategic shift reduced the flexibility of the estate. The indirect sales channels partners required delivery at set prices even in situations where Saint Bernhard suffered from lower yields and therefore less wine availability or higher costs than calculated. As wine sales through B2B channels are realized at lower prices than B2C there is a trade-off between sales and profitability. Although the owners were willing to follow his strategic reorientation and supported his decisions a lack of profitability was a nuisance. Fine-tuning the marketing and sales strategy with focus on channels is needed.